Photojournalism in Brazilian's press transition - Louzada, Silvana (Pontificia Universidad Javeriana - Facultad de Comunicación y Lenguaje, 2006)
The paper deals with the relation between photojournalism and the modernization ofBrazilian's press over the middle of the 20th Century. In this process, known as "reforms", Río de Janeiro's newspapers suffer deep changes in language, such as the adaptation to organizational norms, writing and digging techniques used by the US press, and innovations in language inspired by the modernist movement. This artide traces a short description of the reforms in three newspapers (Diário Carioca, Última Hora , andJornal do Brasil) and discusses the process of changes in journalistic routines and the deontological codes of the profession, seeking dues in order [O understand why the formation la the new generation of pho[Ographic reporters isn't related with, as happened with text jou rnalists, specific formation such as training done in the newspapers, creation of university courses and the requirement of university diploma. En este artículo se discute la relación entre el fotoperiodismo y la modernización de la prensa de Río de Janeiro a mediados del siglo XX. En este proceso de trnasformaciones, conocido como "reformas", los diarios de Río de Janeiro pasanpor profundas transformaciones del lenguaje, tales como la adaptación de normas organizaciones y las técnicas de investigación y redacción utilizadas por la prensa norteamericana, e innovaciones lingüísticas inspiradas en el movimiento modernista.